If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -3x = 7 Combine like terms: -4x + -3x = -7x -7x = 7 Solving -7x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-7'. x = -1 Simplifying x = -1
| n^2-6n-46=0 | | 5a-6-2=12 | | 8u+16=4(u+3) | | 3n=-3 | | 3x+9y=51 | | -6y-12=60 | | -7u+3(u+3)=33 | | -27=3-6w | | 1+6n-3=-14 | | a^2+2a-2=0 | | 9(u-9)=-2u-26 | | 17=3r+2 | | 6q=q-15 | | -5+3x=25 | | -23+5x=-7(-6+x)+7 | | -7w+28=-2(w-9) | | x=10x-2 | | -3a+5a=-6 | | m^2-4m-93=0 | | -7n+3+2n=4n-5+n | | 8e-e=21 | | -28=-4W | | y=60x+35 | | W^2-12w+4= | | x^2=-4.08 | | 2j+2j=-8 | | 2x-5+7x=3x+10 | | 12a=11 | | -2(3x+1)-2x=-3(2x)-2 | | 5e+8e=-78 | | 6u+6u=96 | | 5x-5=x+19 |